Thrombopoietin as Early Biomarker of Disease Severity in Patients With Acute Pancreatitis. Issue 2 (February 2017) - Lupia, Enrico; Pigozzi, Luca; Pivetta, Emanuele; Bosco, Ornella; Vizio, Barbara; Loiacono, Maria; Lucchiari, Manuela; Battista, Stefania; Morello, Fulvio; Moiraghi, Corrado; Mengozzi, Giulio; Montrucchio, Giuseppe
Abstract : Objectives: To study the concentrations of thrombopoietin (TPO), a growth factor recently involved in the pathogenesis of experimental acute pancreatitis (AP), and its potential role as an early diagnostic and prognostic biomarker in patients with AP. Methods: Thrombopoietin was measured in 44 AP patients, 18 patients with nonpancreatic acute abdominal pain, and 18 healthy volunteers. Acute pancreatitis severity was classified on the basis of the 2012 International Atlanta Symposium on Acute Pancreatitis criteria. Results: Thrombopoietin levels did not differ between AP patients and control subjects, whereas these were higher in patients with moderately severe or severe AP compared with those with mild AP. Receiver operating characteristic curve analysis of TPO for severe AP diagnosis showed an area under the curve of 0.80. A cutoff value of 31.48 pg/mL showed the highest sensitivity, allowing to rule out severe AP when TPO was lower, whereas TPO higher than 98.23 pg/mL was associated with severe AP with high specificity (93.5%). Furthermore, TPO levels were greater in AP patients developing organ dysfunction or sepsis and in nonsurvivors compared with survivors. Conclusions: Our data provide the first evidence for TPO as potential early prognostic biomarker in AP patients. High TPO levels at hospital admission may predict organ dysfunction, sepsis, and fatal outcome in AP patients.